Management of Sjogren’s Syndrome Patient: A Case Report of Prosthetic Rehabilitation with 6-Year Follow-Up - Marcos de Mendonça Invernici; Amanda Finger Stadler; Gastão Vale Nicolau; Maria Ângela Naval Machado; Antônio Adilson Soares de Lima; Marilia Compagnoni Martins (Case Reports in Dentistry)
Completely and partially edentulous patients with Sjogren’s syndrome (SS) experience severe hyposalivation, xerostomia, and considerable difficulty in using tissue-supported prosthesis. This clinical paper describes the management, treatment, and 6-year follow-up of a patient diagnosed with SS type II, who uses corticosteroids and antihyperglycemic drugs. The patient received restorative, periodontal, and surgical treatments followed by implant-supported fixed prosthesis. Radiographic evaluation and probing depth showed gingival health and no bone loss after 6 years. Treatment with implant-retained dental prosthesis greatly increased comfort and function, offering an alternative to patients with SS.